Yükseköğretimde Spor Eğitimi Veren Kurumlarda Görev Yapan Akademik Personelin Elektronik Ticaret Hakkındaki Görüşleri, - Yücel, A. S., Karakaya, Y. E., Çoban. B., Gündoğdu, C., Karataş. Ö. (My University, 2012)
In this study the views of the academic personnel working in institutions giving sports training at higher education level in Turkey about electronic trade has been researched. Sample of the study is constituted by 214 academic personnel working in institutions giving sports training at higher education level in Turkey. Validity and reliability study improved by Sevindik (16) was made to determine the views of the participants and “e-Trade User View Form” was used. SPSS 11.5 package program was used in assessment of the questionnaires and t-test, Variance Analysis (ANOVA), Kruskal Wallis Test and LSD test analyses were made. As a result it was observed that, 86% of the academic personnel working in institutions giving sports training at higher education level in Turkey expressed the importance of electronic trade, 81,3% of them expressed that they used electronic banking system and 59,9% of them emphasized that electronic trade eliminates the traditional trade. Furthermore it was determined that there was a significant difference between the views of the participants towards electronic trade according to the variants of sex and education.
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: Internet; Electronic Trade; Academic Personnel; Electronic Banking